Angiotensin Receptor–Binding Protein ATRAP/Agtrap Inhibits Metabolic Dysfunction With Visceral Obesity. Issue 4 (31st July 2013) - Maeda, Akinobu; Tamura, Kouichi; Wakui, Hiromichi; Dejima, Toru; Ohsawa, Masato; Azushima, Kengo; Kanaoka, Tomohiko; Uneda, Kazushi; Matsuda, Miyuki; Yamashita, Akio; Miyazaki, Nobuko; Yatsu, Keisuke; et al.
Abstract : Background: Metabolic disorders with visceral obesity have become a major medical problem associated with the development of hypertension, type 2 diabetes, and dyslipidemia and, ultimately, life‐threatening cardiovascular and renal diseases. Adipose tissue dysfunction has been proposed as the cause of visceral obesity‐related metabolic disorders, moving the tissue toward a proinflammatory phenotype. Methods and Results: Here we first report that adipose tissues from patients and mice with metabolic disorders exhibit decreased expression of ATRAP/ Agtrap, which is a specific binding modulator of the angiotensin II type 1 receptor, despite its abundant expression in adipose tissues from normal human and control mice. Subsequently, to examine a functional role of ATRAP in the pathophysiology of metabolic disorders, we produced homozygous ATRAP deficient ( Agtrap −/− ) mice, which exhibited largely normal physiological phenotype at baseline. Under dietary high fat loading, Agtrap −/− mice displayed systemic metabolic dysfunction, characterized by an increased accumulation of pad fat, hypertension, dyslipidemia, and insulin resistance, along with adipose tissue inflammation. Conversely, subcutaneous transplantation of donor fat pads overexpressing ATRAP derived from Agtrap transgenic mice to Agtrap −/− recipient mice improved the systemic metabolic dysfunction. Conclusions: These results demonstrate that Agtrap −/− mice are an effective model of metabolic disorders with visceral obesity and constitute evidence that ATRAP plays a protective role against insulin resistance, suggesting a new therapeutic target in metabolic disorders. Identification of ATRAP as a novel receptor binding modulator of adipose tissue inflammation not only has cardiovascular significance but may have generalized implication in the regulation of tissue function.